Dynamic analysis of a tension leg platform under extreme waves - Chandrasekaran, Srinivasan; Yuvraj, Koshti (Journal of Naval Architecture and Marine Engineering, 2013)
Recent observations of the sea state that result in the undesirable events confirm the presence of extreme waves like freak waves, which is capable of causing irreparable damages to offshore installations and (or) create inoperable conditions to the crew on board. Knowledge on the extreme wave environment and the related wave-structure interaction are required for safer design of deep-water offshore structures. In the current study, typical long crested extreme waves namely: i) New Year wave at offshore Norway; and ii) Freak wave at North Sea are simulated using the combined wave model. Dynamic response of the Tension Leg Platforms (TLP) under these extreme waves is carried out for different wave approach angles. Based on the analytical studies cared out, it is seen that the TLPs are sensitive to the wave directionality when encountered by such extreme waves; ringing type response is developed in TLPs which could result in tether pull out. DOI: http://dx.doi.org/10.3329/jname.v10i1.14518